Incidental detection of filarial worm in metastatic axillary lymph node from ductal carcinoma breast - Ranjan Agrawal; Parbodh Kumar (Medical Journal of Dr. D.Y. Patil University, 2015)
Filariasis is a major disease of the tropics. Frequently, lymphatics of the lower limbs, retroperitoneal tissues, spermatic cord, epididymis, and mammary glands are involved. Simultaneous filariasis along with another underlying disease is rare. We present a rare case of filariasis of the axillary lymph node in a modified radical mastectomy specimen, which also showed metastatic deposits of ductal carcinoma breast. The case is presented due to its rarity.